Lebanon’s Second Republic: Prospects for the Twenty-First Century by Kail C. Ellis, ed. (Gainesville, FL: University Press of Florida, 2002. 236 pages.) (American Journal of Islam and Society, 2004)
It has now been over a decade since Lebanon’s long civil war ended.Indeed, the new constitutional structures that emerged from the war –Lebanon’s second republic – will soon have a longer life than the waritself. This book examines both the depth and sustainability of Lebanon’snew-found stability and brings together both academics specializing incontemporary Lebanese affairs as well as several Lebanese professionals.It is divided into three sections: Lebanon’s future in the context of theMiddle East peace process, questions of sectarianism and identity withinLebanon, and selected questions relating to social justice and economicperformance in the postwar world. The book is also flanked by an introductionand an epilogue written by Ellis.The volume first examines the regional and global contexts in whichLebanon finds itself. Modern Lebanon has always been vulnerable toexternal interference in its affairs. Hafeez Malik argues that in the nineteenthcentury, it was the competition between the great powers that led to ...